Completeness of notifications by venomous animals accidents: a descriptive study, Brazil, 2007-2019 - Brito, Mariana (2023)
Objective: To describe the completeness of notifications of accidents by venomous animals in the Information System for Notifiable Diseases-Sinan, in Brazil and regions, from 2007 to 2019. Methods: Essential and non-mandatory fields for snakebite notifications were analyzed, araneism and scorpionism, considering the completeness categories Excellent (≤5.0% incompleteness), Good (5.0% to 10.0%), Regular (10.0% to 20.0%), Bad (20,0% and ≤50.0%) and Very bad (>50.0%). Proportional change in completeness between 2007 and 2019 was estimated. Results: 1,871,462 notifications were investigated. The fields “local manifestations”, “systemic”, case classification, case evolution and zone of occurrence presented excellent or good completeness. Schooling and race/color showed regular or poor completeness. Occupancy was predominantly poorly or very poorly filled. Zone, case evolution and education showed a proportional worsening in completeness in most regions (VP<0). Conclusion: There is improvement and completeness in most fields, although socioeconomic and occupational fields demand more attention